Closed-loop handling stability of 4WS vehicle with yaw rate control - Lv, Hongming (Strojniški vestnik, 2013)
To improve the vehicle handling stability, a four-wheel steering (4WS) controller with yaw rate tracking is proposed in this paper. A driver/vehicle closed-loop system is built based on the preview-follower theory to evaluate the systems manoeuvring performance. Next, the system driving on a double lane-change road and on a low adhesion road are simulated and compared with conventional front-wheel steering vehicle. The Fourier transform method is developed to analyse the dynamics of the closed-loop system in the frequency domain. The results show that the proposed 4WS vehicle has the preferred response characteristics of sideslip angle and yaw rate, and is robust regarding tire cornering stiffness, which guarantees the handling stability in emergency braking condition.
Keywords: bočna vodljivost; closed-loop system; drivers; four-wheel steering; handling stability; hitrost vrtenja okrog navpične osi; štirikolesno krmiljenje; vehicle; vozila; vozniki; yaw rate; zaprtozančni sistem